Hubungan Tingkat Pengetahuan, Sikap dan Praktik Merokok dengan Kejadian ISPA di Pemondokan Putra RW 51 Pogung Rejo, Sleman, Yogyakarta - Tiara Putri Prabawati; Achmad Husein; sri Muryani (Sanitasi: Jurnal Kesehatan Lingkungan, 2014)
In Indonesia, in addition to its escalating production, cigarette becomes the most consumed co-modity, after rice, eventhough it has already known that it contains some chemical substances harmful for human health. Based on a preliminary survey interviewing fifteen people live in male boarding houses located at RW 51 of Pogung Rejo, in Sleman, it was revealed that most of them were smoker, although they had good level, both of knowledge and the concerned attitude. To understand the relationship between knowledge level, attitude and practice of cigarette smoking, with the incidence of acute respiratory infection (ARI) among male boarders in that area, a cross sectional approached survey was conducted. From the total population, 20 % (57 individual) of boarders were selected by using accidental sampling technique as respondents of the study. The data were collected directly by questionnaire-led interview and check-listed observation. Descriptively, it was identified that 57,8 % of respondents were showing of ARI symptoms, and related with the independent variables, it was also found that 50,9 % had low level of knowledge, 57,9 % had not-good attitude, and 70,2 % were smokers. Statistical analysis by employing chi-square test at 95 % confidence level to measure the relationships between those three variables with ARI incidence, yielded p-values of 0,516; 0,034 and 0,024 respectively. The subsequent analysis for calculating the corresponding prevalence ratios gave 1,16 for level of knowledge, 1,67 for the attitude, and 1,91 for cigarette smoking practice.